Hubungan Dukungan Keluarga Dengan Kualitas Tidur Lansia Pasca Stroke Di Masa Pandemi Covid-19 - Tasya Putri Widyastika; Reni Zulfitri; Musfardi Rustam (Jurnal Vokasi Keperawatan (JVK), 2023)
The elderly are individuals aged 60 years and over. The increasing number of elderly causes problems in health aspects such as disease attacks, one of which is stroke. The impact of stroke causes the elderly to experience many problems such as decreased sleep quality. Family support is important in the recovery and healing process. The purpose of this study was to determine the relationship between family support and sleep quality in the elderly after a stroke during the Covid-19 pandemic. This study used a cross sectional. The number of samples used in this study were 64 people who were taken using a total sampling technique. Data collection was taken using a family support questionnaire where the questionnaire has been tested for validity and reliability and using the Pittsburgh Sleep Quality Index. Analysis of the data used is univariate and bivariate using Chi Square. The results showed that the family support in this study was high (81.3%). Based on the dimensions of high family support is instrumental support (100%). While the results of the sleep quality of the elderly after stroke in this study were good (71.9%). Bivariate analysis showed that p-value (0.02) < (0.05) where there was a significant relationship between family support and sleep quality for the elderly after stroke in the work area of ​​Simpang Tiga Health Center. The results of this study found that family support affects the sleep quality of the elderly after stroke.